2021
DOI: 10.1093/infdis/jiab033
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Transgenic Mice Are Resistant to Chronic Wasting Disease Prions From Norwegian Reindeer and Moose

Abstract: Chronic wasting disease (CWD) is the transmissible spongiform encephalopathy or prion disease affecting cervids. In 2016 the first cases of CWD were reported in Europe in Norwegian wild reindeer and moose. The origin and zoonotic potential of these new prion isolates remain unknown. In this study to investigate zoonotic potential we inoculated brain tissue from CWD-infected Norwegian reindeer and moose into transgenic mice overexpressing human prion protein. After prolonged post-inoculation survival periods no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 15 publications
(37 reference statements)
2
27
0
Order By: Relevance
“…Primary passage of transmission experiments into humanized mice (transgenic mice expressing the human PRNP gene) with isolates from three of the Norwegian cases (one moose, one reindeer, and one red deer) were reassuringly negative, suggesting a strong transmission barrier to humans, as previously reported for North American CWD [ 104 ]. However, further investigations are ongoing, with several Norwegian CWD isolates and different lines of humanized mice.…”
Section: Cwd In Norwegian Reindeermentioning
confidence: 58%
“…Primary passage of transmission experiments into humanized mice (transgenic mice expressing the human PRNP gene) with isolates from three of the Norwegian cases (one moose, one reindeer, and one red deer) were reassuringly negative, suggesting a strong transmission barrier to humans, as previously reported for North American CWD [ 104 ]. However, further investigations are ongoing, with several Norwegian CWD isolates and different lines of humanized mice.…”
Section: Cwd In Norwegian Reindeermentioning
confidence: 58%
“…The highly efficient peripheralization of CWD in NA deer and elk and resultant prion infectivity in skeletal muscle and other materials destined for consumption by humans [ 9 , 35 ], their ability to template in vitro conversion of human PrP [ 68 , 69 ], and the emerging results of transmission studies in non-human primates [ 70 – 72 ] elicit additional concern. As alluded to above, our findings in GtE226 and GtQ226 mice detailing the importance of peripheral PrP expression force us to reconsider the precision of Tg mice expressing human PrP for assessing zoonotic transmission of CWD [ 73 76 ] and suggest that Gt models provide an improved platform for making this determination. Unfortunately, previously generated knock-in mice designed to be susceptible to human prions had long incubation times and incomplete attack rates; similarly constructed knock-in mice designed to be susceptible to BSE were paradoxically less responsive to this strain than their wild type mouse counterparts [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their recent identification, many studies are still ongoing and needed to assess the zoonotic risks associated with the Scandinavian CWD strains and help determining strategies to limit their impact on the wild and farm-populations. Recently, it was shown that humanized mice resisted infection with these agents (primary passage negative) [80]. A larger set of experiments, including (i) transgenic models in which peripheral replication can be addressed because prion zoonosis can be tissue specific [67], (ii) a larger panel of CWD isolates from different species because it can impact the transmission properties as exemplified with sheep-passaged BSE [81], are necessary to conclude on the zoonotic potential of CWD prions.…”
Section: Interspecies Transmission Of Cwdmentioning
confidence: 99%